Ethiopia can be Africa's 'breadbasket' as well as its 'water tower' - Duncan, Alan J. (2011)
ILRI's Alan Duncan was asked to share a Nile Basin Development Challenge (NBDC) 'story' at the recent International Forum on Water and Food. Alan's story introduces some of the challenges that the Ethiopian Government faces in seeking to improve natural resources management at the local level, in the Blue Nile Basin. He reports that the sectors need to be better connected (water, agriculture, livestock); and more dialogue between officials and communities towards more participatory approaches to rainwater management. One approach the NBDC is trying is to support local 'innovation platforms' - spaces for diverse actors to come together to engage in dialogue, to jointly identify and address issues. The idea is that these will catalyze greater local participation and ownership of interventions, connect with national initiatives, and help make Ethiopian landscapes more productive. He concludes stating that Ethiopia is known as the 'water tower' of Africa ... with strong community participation and ownership, it could also be Africa's breadbasket!